A NEW NEMATODE OF THELASTOMATIDAE FROM A BURROWING INSECT - SHANJOY, LAISHRAM; GAMBHIR, R. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
In a taxonomic investigation of insect parasitic nematodes during the month of February, 2019 at Khordak village of Thanga, Manipur, many nematodes were recovered. Among them, one of the specimens belonging the genus Cameronia was found to present many morphological characters that are different from the other already known species.The genus Cameronia was established by Basir, 1948 with Cameronia biovata as its type species recovered from the insect Gryllotalpa africana. This present newly recovered specimen is characterised by the presence of single annule around the mouth opening, followed by a large prominent second annule, with many small spine like structures seen each and every junction of successive cephalic annules up to the end of oesophagus. Body annules are faintly visible. The eggs are elliptical and elongated. The present specimen come closer to the three known species of the genus Cameronia viz. C. triovata, C. manipurensis and C. meerutensis. The comparative study however reveals many differences from the three species, mainly on their morphological structure. After considering the main points of differences, the present specimen has not to be accommodated under any known species but as a new species under the genus Cameronia and proposing a new name of species as Cameronia conoides n.sp. on the basis of conoid shaped tail.